2021
DOI: 10.1155/2021/9917772
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Digitization of Manufacturing Will Enhance the Competitiveness of the Value Chain Based on Advantage Comparison

Abstract: This paper uses WIOD data to calculate and analyze the dominant comparative advantage of Chinese manufacturing global value chain (GVC) based on the WWZ method and empirically studies the influence of digitization on the competitiveness of manufacturing GVC. The main findings are as follows: (1) The competitiveness of Chinese manufacturing GVC has been improved as a whole. The GVC competitiveness of different types of industries is quite different: GVC in middle- and low-knowledge-intensive industries have the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…From the perspective of global economic growth in the past 40 years, there is a big difference between countries with higher forward and backward participation in GVCs based on comparative advantages. Sampatha and Vallejob [25] found that countries that mainly trade in intermediate goods have a higher degree of forwarding participation in the division of labor in the GVC. Their products have a higher level of export technology and added value.…”
Section: Theoretical Mechanism Of the Division Of Labor And Level Of ...mentioning
confidence: 99%
“…From the perspective of global economic growth in the past 40 years, there is a big difference between countries with higher forward and backward participation in GVCs based on comparative advantages. Sampatha and Vallejob [25] found that countries that mainly trade in intermediate goods have a higher degree of forwarding participation in the division of labor in the GVC. Their products have a higher level of export technology and added value.…”
Section: Theoretical Mechanism Of the Division Of Labor And Level Of ...mentioning
confidence: 99%
“…As one of the world's largest manufacturing powers, China's manufacturing industry has always played a crucial role in the Chinese economy [45]. The advancement of this industry not only assumes a critical role in fostering domestic economic growth but also holds a significant stance in the realm of international trade [46].…”
Section: Manufacturing Sector In the Chinese Economymentioning
confidence: 99%
“…Li et al believe that the continuous digital technology revolution can improve the coordination between business strategy and digital technology, hence fostering corporate growth [12]. From the perspective of global value chains, Wu et al assert that the digitization of the manufacturing industry will improve the comparative advantage and competitiveness of the country in the global value chain [13]. In a competitive context, firms launch digital innovation mechanisms, and digital innovation can also alter the competitive climate in which enterprises operate [14].…”
Section: Related Workmentioning
confidence: 99%